Metabolomic Biomarkers Differentiate Soy Sauce Freshness under Conditions of Accelerated Storage. (5th May 2021) - Reddy, Thiruchelvi R.; Overmyer, Katherine A.; Coon, Joshua J.; Drake, MaryAnne; Horiba, Taro; Rankin, Scott A.
Abstract : Naturally fermented soy sauce is one of the few globally valued food condiments. It is complex in its substrate, manufacturing processes, and chemical profile of salts and organic compounds, resulting from spontaneous, enzymatic and biochemical reactions. The overall chemical character of soy sauce has a few rivals relative to its chemical and bioactive complexity. Resulting from this complexity are unique sensory attributes contributing to the characteristic soy sauce flavor as well as potentiating other sensory sensations. Soy sauce is susceptible to deterioration after bottling during storage. This work examined soy sauces over an eight-month period using descriptive sensory methods and the discovery of metabolomic biomarkers with high resolution mass spectrometry, wherein samples were derivatized to enable volatility and identification of polar analytes. While several thousand metabolites were detected, only organic acids, amino acids, and various glycosylated metabolites were statistically defensible biomarkers of storage time. The relationships between sensory and metabolomic data were assessed using Kendall rank-based correlations to generate Kendall Tau correlation coefficients. A second approach filtered the data based on correlation significance and grouped molecules based on hierarchical clustering. Mass spectrometry analyses discovered several thousand unique analyte peaks with relevant changes denoted as significant relative to the fresh samples using volcano depictions of p values versus changes in compound abundances. We present a metabolomic approach for the analysis of complex food systems capable of differentiating a quantifiable extrinsic variable, which is, in this case, storage time with a correlation coefficient of 0.99. We further demonstrate that changes in soy sauce resulting from storage are characterized by sensory decreases in fruity/grape and nutty/sesame aroma and increases in methional/potato aroma and astringent attributes with concomitant changes in the concentrations of several key biomarkers.